Boris Anatolijovych Pustovoyt - «SISJP NAMS», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to the 70th anniversary of the birth of the Head of the Department of Physical Therapy of the Kharkiv State Academy of Physical Culture, Doctor of Medical Sciences, Professor Pustovoyt B. A.